Effect of Water Stess on Growth, Nodulation and Nitrogen Fixation in Causarina Equisetifolia - Kant, Shri; Narayana, H S (Annals of Arid Zone, 2016)
The seedlings of Casuarina equisetifolia were subjected to different degrees of water dress. The shoot and root lengths, the shoot and root weights, nodule size and number, nodule weight, and the amount of nitrogen fixed decreased with the increase in water stress. There was no degeneration of nodules and cessation of nitrogen fixation when the soil moisture was raised to the field capacity once in 72 hours. The reduction in the number of nodules in various degrees of water stress might have be:n brought about through inhibition by water stress.